Sporoderm-removed Ganoderma lucidum spores ameliorated early depression-like behavior in a rat model of sporadic Alzheimer’s disease - Zhao, Yan; Qin, Yu; Hu, Xiao; Chen, Xi; Jiang, Yan-Ping; Jin, Xue-Jun; Li, Gao; Li, Zhen-Hao; Yang, Ji-Hong; Cui, Su-Ying; Zhang, Yong-He (Frontiers in Pharmacology, 2024)
Introduction:Ganoderma lucidum: (G. lucidum, Lingzhi) is a medicinal and edible homologous traditional Chinese medicine that is used to treat various diseases, including Alzheimer’s disease and mood disorders. We previously reported that the sporoderm-removed G. lucidum spore extract (RGLS) prevented learning and memory impairments in a rat model of sporadic Alzheimer’s disease (sAD), but the effect of RGLS on depression-like behaviors in this model and its underlying molecular mechanisms of action remain unclear. Method: The present study investigated protective effects of RGLS against intracerebroventricular streptozotocin (ICV-STZ)-induced depression in a rat model of sAD and its underlying mechanism. Effects of RGLS on depression- and anxiety-like behaviors in ICV-STZ rats were assessed in the forced swim test, sucrose preference test, novelty-suppressed feeding test, and open field test. Results: Behavioral tests demonstrated that RGLS (360 and 720 mg/kg) significantly ameliorated ICV-STZ-induced depression- and anxiety-like behaviors. Immunofluorescence, Western blot and enzyme-linked immunosorbent assay results further demonstrated that ICV-STZ rats exhibited microglia activation and neuroinflammatory response in the medial prefrontal cortex (mPFC), and RGLS treatment reversed these changes, reflected by the normalization of morphological changes in microglia and the expression of NF-κB, NLRP3, ASC, caspase-1 and proinflammatory cytokines. Golgi staining revealed that treatment with RGLS increased the density of mushroom spines in neurons. This increase was associated with elevated expression of brain-derived neurotrophic protein in the mPFC. Discussion: In a rat model of ICV-STZ-induced sAD, RGLS exhibits antidepressant-like effects, the mechanism of which may be related to suppression of the inflammatory response modulated by the NF-κB/NLRP3 pathway and enhancement of synaptic plasticity in the mPFC.